'Underlying Energy Efficiency' in the US - Massimo Filippini; Lester C. Hunt (ETH Zurich, CER-ETH - Center of Economic Research, 2013)
The promotion of US energy efficiency policy is seen as a very important activity by the Energy Information Agency (EIA). Generally, the level of energy efficiency of a state is approximated by energy intensity, commonly calculated as the ratio of energy use to GDP. However, energy intensity is not an accurate proxy for energy efficiency, because changes in energy intensity are a function of changes in several factors including the structure of the economy, climate, efficiency in the use of resources and technical change. The aim of this paper is to measure the `underlying energy efficiency' for the whole economy of 49 `states' in the US using a stochastic frontier energy demand approach. A total US energy demand frontier function is estimated using panel data for 49 `states' over the period 1995 to 2009 using several panel data models: the pooled model; the random effects model; true fixed effects model; the true random effects model; and the Mundlak versions of the pooled and random effects models. The analysis confirms that energy intensity is not a good indicator of energy efficiency; whereas, by controlling for a range of economic and other factors, the measure of `underlying energy efficiency' obtained via the approach adopted here (based on the microeconomic theory of production) is.
Keywords: D; D2; Q; Q4; Q5; 330; US total energy demand; efficiency and frontier analysis; state energy efficiency